2002
DOI: 10.1128/aac.46.3.695-701.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activities of Alkylphosphocholines against Clinical Isolates of Acanthamoeba spp

Abstract: Free-living amoebae of the genus Acanthamoeba are causing serious chronic conditions such as destructive keratitis in contact lens wearers or granulomatous amoebic encephalitis in individuals with compromised immune systems. Both are characterized by the lack of availability of sufficiently effective and uncomplicated, manageable treatments. Hexadecylphosphocholine (miltefosine) is licensed for use as a topical antineoplastic agent, but it is also active in vitro against several protozoan parasites, and it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 30 publications
2
84
1
1
Order By: Relevance
“…74 Walochnik et al 73 found that APC-1, out of eight compounds with increasing chain length, had the highest level of amoebicidal activity similar to findings of others for Leishmania sp. and T. cruzi.…”
Section: Alkylphosphocholinesmentioning
confidence: 91%
See 1 more Smart Citation
“…74 Walochnik et al 73 found that APC-1, out of eight compounds with increasing chain length, had the highest level of amoebicidal activity similar to findings of others for Leishmania sp. and T. cruzi.…”
Section: Alkylphosphocholinesmentioning
confidence: 91%
“…73 This group of compounds consists of phosphocholine esterified to long-chain aliphatic alcohols exhibiting in vitro and in vivo antineoplastic activities. In addition, they are active against protozoan parasites such as Leishmania donovani, Trypanosoma cruzi, and Entamoeba histolytica.…”
Section: Alkylphosphocholinesmentioning
confidence: 99%
“…The drug was also active against Trypanosoma brucei, Entamoeba histolytica, Acanthamoeba spp. and T. cruzi (Croft et al 1996;Konstantinov et al 1997;Seifert et al 2001;Walochnik et al 2002), and it was shown that miltefosine affects apicomplexan parasites such as Plasmodium falciparum and Cryptosporidium (Pessi et al 2004;Shahiduzzaman et al 2009). Similar to many of the above-mentioned protozoan parasites, Neospora occupies an intracellular niche, indicating that miltefosine might also be useful for the treatment neosporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of action of miltefosine against Leishmania parasites involves the interaction with membrane phospholipids and sterols, and the drug interferes with the functionality of a number of enzymes involved in phospholipid metabolism such as protein kinase C and the phospholipases A, C and D, finally leading to apoptosis (Barratt et al 2009). Hexadecyltrimethylammonium bromide, a compound structurally similar to miltefosine, was demonstrated to exhibit potent in vitro activity against Plasmodium falciparum (Walochnik et al 2002;Schuster et al 2006;Choubey et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Current therapeutic agents include a combination of drugs including ketoconazole, fluconazole, sulfadiazine, pentamidine isethionate, fluorcytosine, amphotericin B, trifluorperazine or thiroridizine, clarithromycin, azithromycin, itraconazole, or rifampin that may be effective against CNS infections due to free-living amoebae but have severe side effects. Recent studies have suggested that alkylphosphocholine compounds, such as hexadecylphosphocholine exhibit anti-amoebic properties as well as cross the blood-brain barrier, thus may have value in the treatment of GAE [10,11] . Even with treatment, survivors may develop disability such as hearing loss, vision impairment etc.…”
Section: Clinical Diagnosis Of Gaementioning
confidence: 99%